2013
DOI: 10.1371/journal.pone.0070087
|View full text |Cite
|
Sign up to set email alerts
|

Functional Loss of Two Ceramide Synthases Elicits Autophagy-Dependent Lifespan Extension in C. elegans

Abstract: Ceramide and its metabolites constitute a diverse group of lipids, which play important roles as structural entities of biological membranes as well as regulators of cellular growth, differentiation, and development. The C. elegans genome comprises three ceramide synthase genes; hyl-1, hyl-2, and lagr-1. HYL-1 function is required for synthesis of ceramides and sphingolipids containing very long acyl-chains (≥C24), while HYL-2 is required for synthesis of ceramides and sphingolipids containing shorter acyl-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 40 publications
1
64
0
Order By: Relevance
“…Many known lifespan regulators, such as daf-16 and mir-71, play positive roles in both lifespan extension and L1 starvation survival (Baugh and Sternberg 2006;Kenyon 2010;Pincus et al 2011;Zhang et al 2011b;Boulias and Horvitz 2012). However, a previous publication showed that C. elegans strains with mutations in both hyl-1 and lagr-1 genes, like our CerS(rf) mutants, displayed autophagy-dependent lifespan extension under wellfed conditions (Mosbech et al 2013). It has also been shown that, while the hyl-2(lf) mutant was sensitive to anoxia, the hyl-1(lf) mutant was resistant to anoxia (Menuz et al 2009).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Many known lifespan regulators, such as daf-16 and mir-71, play positive roles in both lifespan extension and L1 starvation survival (Baugh and Sternberg 2006;Kenyon 2010;Pincus et al 2011;Zhang et al 2011b;Boulias and Horvitz 2012). However, a previous publication showed that C. elegans strains with mutations in both hyl-1 and lagr-1 genes, like our CerS(rf) mutants, displayed autophagy-dependent lifespan extension under wellfed conditions (Mosbech et al 2013). It has also been shown that, while the hyl-2(lf) mutant was sensitive to anoxia, the hyl-1(lf) mutant was resistant to anoxia (Menuz et al 2009).…”
Section: Discussionmentioning
confidence: 75%
“…Ceramide has been studied for its role in apoptosis and the response to certain stresses such as anoxia, cytokines, toxins, and chemotherapeutic agents (Deng et al 2008;Hannun and Obeid 2008;Menuz et al 2009;Nikolova-Karakashian and Rozenova 2010;Mosbech et al 2013;Cutler et al 2014;Liu et al 2014). Most of these studies were carried out in nutrient-rich conditions, while the roles of ceramide under fasting conditions in whole organisms remain to be investigated.…”
mentioning
confidence: 99%
“…These results directly link mmBCFA to a new signaling pathway. Other publications demonstrated that ceramides are required for anoxia protection [42], autophagy dependent life span extension [43] or radiation induced apoptosis [44].…”
Section: Sphingolipidsmentioning
confidence: 99%
“…One of the differences between these two fatty acids is that only palmitate contributes to the cellular synthesis of ceramide, a lipid species that has been shown to decrease AMPK activity and contribute to vascular dysfunction (91,94). Ceramide and its metabolite, sphingosine-1-phosphate, have been suggested to have opposing roles in autophagy regulation, but whether ceramide accumulation induces or impairs basal autophagy in HAECs remains unclear (70,84). Since ceramide may potentially regulate both AMPK and autophagy, we hypothesized that, in the presence of palmitate, ceramides may prevent activated AMPK from phosphorylating ULK1 and inducing autophagy.…”
Section: Activation Of Ampk Does Not Restore Autophagy In a Nutrient-mentioning
confidence: 99%